Narrow identity resources for future students: the 21st century skills movement encounters the Norwegian education policy context. Issue 3 (4th May 2019) - Hilt, Line T.; Riese, Hanne; Søreide, Gunn Elisabeth
ABSTRACT: 21st century skills is a global network of corporate and governmental influences that promotes competences suited to fit the future knowledge economy. Through a discourse analysis of an influential Official Norwegian Report, 'The School of the Future. Renewal of Subjects and Competences' (NOU 2015:8), this paper explores how ideas of 21st century skills are translated into the Norwegian education policy context. Firstly, the paper analyses the context-specific reasons for receptiveness by investigating discursive warrants . Secondly, the paper identifies how the policy document constructs a set of preferred subject positions that constitute an image of an ideal student. Thirdly, the paper investigates the discursive framing of these subject positions. We find that the policy document constructs an image of an ideal student who is creative, responsible, cooperative, engaged, self-regulated and in complete control of herself, her learning and her future. This image draws on more pronounced neo-liberal discourses, but also well-established discourses in the Norwegian context, such as social democratic progressivism. This intertwining of discourses shows how traits of homogeneity related to global ideas, as well as heterogeneity related to the Norwegian policy context, are both visible in the Norwegian translation of 21st century skills.